Da'wah and Social Change in Islamic Organizations: Muhammadiyah and Its Elements - Roni Rodiana; Imron Rosidi (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
The actualization of the da'wah system is accompanied by a series of complex problems, namely first, when Islamic da'wah is delivered in a society that is not yet Islamic, the message of Islam is seen by the local community as foreign/newcomers. Second, that the ownership of Islam as a result of da'wah activities runs slowly or quickly. Third, when socio-cultural changes become more complex, causing humanitarian problems to become more widespread, Islamic da'wah is faced with the obligation to provide clear answers regarding human interests in various aspects of life. This research was conducted to understand the concept of Muhammadiyah da'wah in the aspect of upholding al-Khair, inviting al-Ma'ruf and preventing al-Munkar, in order to realize social change that leads to the goals and ideals of Islamic da'wah. It can be concluded that 1) there is a need for massive outreach regarding the function of da'wah which has a role in social change; 2) One of the functions of da'wah in social change is the realization of a society that increases its religiousness; 3) In order for this to be implemented, careful planning is needed, one of which is by conducting studies on various approaches that attract the attention of the public, including: lectures, discussions and questions and answers. Keywords: Da'wah, ma'ruf, Muhammadiyah, munkar, Social Change. Abstrak Aktualisasi sistem dakwah disertai dengan serangkaian masalah yang kompleks, yakni pertama, ketika dakwah Islam disampaikan dalam masyarakat yang belum Islam, pesan Islam oleh masyarakat setempat dipandang asing/pendatang. Kedua, bahwa pemilikan Islam sebagai hasil kegiatan dakwah berjalan secara lambat atau secara cepat. Ketiga, ketika perubaan sosio-kultural semakin kompleks menyebabkan masalah kemanusiaan semakin meluas, dakwah Islam dihadapkan dengan keharusan memberikan jawaban yang jelas menyangkut kepentingan manusia dalam berbagai segi kehidupan. Penelitian ini dilakukan untuk memahami konsep dakwah Muhammadiyah pada aspek menegakkan al-Khair, mengajak al-Ma’ruf dan mencegah al-Munkar, agar terwujudnya perubahan sosial yang mengarah kepada tujuan dan cita-cita dakwah Islam. Diperoleh kesimpulan bahwa 1) Perlunya sosialisasi yang massif mengenai fungsi dakwah yang memiliki peran dalam perubahan sosial; 2) Salah satu fungsi dakwah dalam perubahan sosial adalah terwujudnya masyarakat yang meningkat kereligiusannya; 3) Agar itu dapat terlaksana maka perlu perencanaan yang matang, salah satunya dengan menyelenggarakan kajian-kajian berbagai pendekatan yang menarik perhatian masyarakat, diantaranya: ceramah, diskusi dan tanya jawab. Kata kunci: Da’wah, ma’ruf, Muhammadiyah, munkar, Social Change.